Flotation Costs and the Weighted Average Cost of Capital - Ezzell, John R.; Porter, R. Burr (Journal of Financial and Quantitative Analysis, 1976)
The weighted average cost of capital (Ko) is presented in virtually all textbooks in financial management and capital budgeting as a practical concept fundamental to the actual selection of optimal financial and investment alternatives. As often employed Ko can be defined aswhereKo = the weighted average cost of capital, Ks = the cost of equity capital, Kb = the cost of debt capital, S = the market value of the firm's equity, B = the market value of the firm's debt, andV = S + B, the total market value of the firm.